Audacious euphony chromatic harmony and the triad's second nature - Cohn, Richard Lawrence 1955- (Oxford University Press, 2012)
Reconstructing historical conceptions of harmonic distance 'Audacious Euphony' advances a geometric model appropriate to understanding triadic progressions characteristic of 19th-century music
Includes bibliographical references and index
Keywords: Geschichte 1800-1900; Harmony; Triads (Music); Harmonielehre; Dreiklang